MOLECULAR DOCKING TURUNAN KALKON TERHADAP RESEPTOR ESTROGEN B (ER- B) SEBAGAI ANTIKANKER PAYUDARA - Dwi Koko Pratoko (Jurnal Kimia Terapan Indonesia, 2012)
Estrogen receptor-S (ER- ft) was also shown to be the important factor to inhibits proliferation and invasion of breast cancer cells. Estrogen receptor-S complexed with genistein is taken as a role model to target the drug action. Docking molecule chalcone derivatives on Estrogen receptor-S have been done to test the docking energy that associated with binding affinity between ligand and receptor. Based on docking result, Kalkon XII has shown best docking energy (MoIDockScore). Thus Kalkon XII can be synthesized and usedfor in vitro cytotoxic activity.